1997
DOI: 10.1111/j.1469-7998.1997.tb02806.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival and behaviour of castrated Soay sheep (Ovis aries) in a feral island population on Hirta, St. Kilda, Scotland

Abstract: With 5 figures in the text)The free-living population of Soay sheep on the island of Hirta, St. Kilda, in the Outer Hebrides, has been intensively studied since 1959. The present study was initiated to throw light on the causes of the high mortality rate of adult rams in comparison to that of ewes. In 1978, 1979 and 1980, a total of 72 male lambs was castrated within a day or two of birth. The survival of these castrates has been much longer than that of the entire rams, marked as controls, and longer than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 22 publications
5
24
0
Order By: Relevance
“…This is particularly interesting, as the pressure of the rut is expected to be much lower in captivity, where usually only one adult male is kept in a harem, when compared with the situation in the wild, where several males compete for the females. In one experimental study on wild-living soay sheep (Ovis aries), castrated males demonstrated a prolonged LE compared with intact males and even females [26]. Both findings together support speculations that not only an intensive intraspecific competition for females during the rut, but also reproductive physiology per se has a negative influence on male LE.…”
Section: Discussionsupporting
confidence: 72%
“…This is particularly interesting, as the pressure of the rut is expected to be much lower in captivity, where usually only one adult male is kept in a harem, when compared with the situation in the wild, where several males compete for the females. In one experimental study on wild-living soay sheep (Ovis aries), castrated males demonstrated a prolonged LE compared with intact males and even females [26]. Both findings together support speculations that not only an intensive intraspecific competition for females during the rut, but also reproductive physiology per se has a negative influence on male LE.…”
Section: Discussionsupporting
confidence: 72%
“…Adult male ungulates typically stop feeding during the rut (e.g. Jewell 1997), and this could be expected to affect the morphology of the rumen. However, all of our winter samples were collected after the rut and most of the papilla variables that we measured in that season were slightly greater for males than for females, suggesting that the rut had relatively small and/or short-term effects on the rumen morphology of male tahr.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, male mating effort is often associated with lower survival (e.g., red deer, Clutton-Brock et al 1982; elephant seals, Mirounga angustirostris , Clinton and LeBoeuf 1993; Columbian ground squirrels, Spermophilus columbianus , Neuhaus and Pelletier 2001). By contrast, castration can significantly extend male lifespan (e.g., Soay sheep, Ovis aries , Jewell 1997). In ground squirrels with seasonal reproduction, male mortality is generally high during or after the mating season, whereas female mortality is high in conjunction with the birth season and lactation (Michener and Locklear 1990; Michener 1998; Neuhaus and Pelletier 2001).…”
Section: Introductionmentioning
confidence: 99%